Reclamation in southern China: The early Chu’s agriculture revealed by macro-plant remains from the Wanfunao site (ca. 1000–770 BCE) - Yang, Ruichen; Tang, Liya; Zhao, Dong; Huang, Wenxin; Luo, Yunbing (Frontiers in Plant Science, 2022)
The Wanfunao site was a large Chu settlement in Zhou Dynasty. It was located on an alluvial plain along the Yangtze River in the Yichang section. The region around the site comprised mountains, hills, and plains, which was a compatible environment for the cultivation of various crops. Previous studies have suggested that the middle and lower reaches of the Yangtze River are one of the most productive regions for rice cultivation. Besides rice, however, seven dryland crops have been found at the Wanfunao site: foxtail millet, broomcorn millet, wheat, barley, oat, buckwheat, and adzuki bean. Among them, foxtail millet and rice are most ubiquitous. The crop assemblage has revealed that the northern dryland crops, including those were newly adapted cereals such as foxtail millet, wheat, and barley, gradually dispersed southward and became a part of the diet along with rice. This can be attributed to southern Chinese inhabitants’ reclamation of the hilly environment for agriculture. Although communities in southern China had cultivated rice on the plains for thousands of years, newly introduced dryland crops from north China adapted to mountainous environments better. The development of multi-cropping systems in southern China likely involved changes in agricultural ontology associated with the adaptation of northern crops in southern environments newly encountered. Additionally, the assemblage of foxtail millet grain/rice spikelet base in the site may have been used for livestock feeding. A wide range of landforms, compatible farming, and surplus agricultural products for husbandry may have been a part of the economic foundation that facilitated the rise of Chu.